STUDENTS' SAVING BEHAVIOUR: WHAT ARE THE MOTIVES THAT INFLUENCE THEM TO SAVE? - Hartono, Ulil; Isbanah, Yuyun (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
This study aims to determine the determinants of saving behavior using financial literacy as a mediating variable. The endogenous variable in this study was saving behavior, while the exogenous variables were financial literacy, parental socialization, peer influence, and self-control. The respondents were 300 students from the Faculty of Economics of Indonesia. Data were analyzed by Structural Equation Modelling (SEM) using STATA software. The results show that parental socialization and peer influence positively affect financial literacy, whereas self-control does not. Financial literacy directly affects saving behavior. Parental socialization and peer influence directly influence saving behavior.   The results provide a new understanding of the importance of financial literacy in encouraging student-saving behavior.   The role of parents and peers in the environment is essential for improving students"™ financial literacy and saving behavior. The banking industry can play a role in increasing financial literacy through collaboration with universities through a virtual account program and the socialization of savings to students. It is also an opportunity for saving service providers to introduce their products to consumers early.JEL : G41, G410.ABSTRAKTujuan penelitian ini untuk mengetahui determinan dari saving behaviour dengan menggunakan financial literacy sebagai variabel mediasi. Variabel endogen dalam penelitian ini adalah saving behaviour sedangkan variabel eksogen, yaitu financial literacy, parental socialization, peer influence, dan self-control. Responden penelitian ini adalah 300 mahasiswa Fakultas Ekonomi di Indonesia. Data dianalisis dengan Structural Equation Modeling (SEM) menggunakan software STATA. Hasil penelitian menunjukkan bahwa parental socialization dan peer influence berpengaruh positif terhadap financial literacy, sedangkan self-control berpengaruh negatif terhadap financial literacy. Financial literacy juga terbukti berpengaruh secara langsung pada saving behaviour. Parental socialization dan peer influence juga memiliki pengaruh langsung pada saving behaviour. Penelitian ini memberikan pemahaman baru mengenai pentingnya literasi keuangan untuk mendorong perilaku menabung bagi mahasiswa. Peran orang tua dan teman sebaya menjadi faktor penting dalam menumbuhkan literasi keuangan dan perilaku menabung mahasiswa. Industri perbankan dapat berperan dalam meningkatkan financial literacy melalui kerjasama dengan universitas dalam bentuk program virtual account sekaligus untuk sosialisasi tabungan ke mahasiswa. Ini juga menjadi peluang bagi penyedia layanan tabungan untuk memperkenalkan produknya ke konsumen lebih dini.Kata Kunci: literasi keuangan, peer influence, parental socialization, self-control, saving behaviour.